The role of social networking sites in destabilizing societal peace and the public’s attitude towards them (A field study on a sample of young people in the city of Latakia) - البائع, نورا; يسرا زريقة, (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the research was to identify the role of social networking sites in destabilizing societal peace and the public’s attitude towards it. The research used the descriptive analytical method, and the research sample was composed of 60 members of the social networking sites’ audience (30 university students, 30 from outside the university). A research tool consisting of 4 parts was built, and the validity and reliability of the tool was confirmed after it was presented and judged by a group of arbitrators. The research reached the following results: The percentage of WhatsApp users is the largest, that Facebook came in second place, and YouTube in third place, and that there are a number of sites whose frequency of use by the sample was (0). The percentage of users of social networking sites was ranked first (from one to two hours), in second place (less than an hour), in third place (from two to four hours), and in last place (more than four hours). There are differences in the opinions of the research sample on the questionnaire items (the role of social networking sites in destabilizing societal peace) for the benefit of current university students. The public in general is positively oriented towards (the role of social networking sites in destabilizing societal peace). Keywords: social networking sites, societal peace.